Consumer Behavior in Food Delivery Applications: A Systematic Literature Review and Future Research Agenda - Liu, Xin; Ng, Siew Imm; Basha, Norazlyn Kamal; Cheah, Jun-Hwa (Advances in Social Sciences Research Journal, 2024)
Over the past few years, there has been notable interest among consumers in food delivery applications. Consequently, understanding consumer behavior within this context has become crucial for practitioners seeking to execute effective marketing strategies. While academic studies in this field are gaining traction, there remains a lack of a comprehensive overview. Existing literature on the subject is often fragmented and inconsistent, hindering a thorough comprehension of consumer behavioral patterns in food delivery applications. Thus, this study aims to address this gap by conducting a systematic literature review to organize and synthesize current knowledge on consumer behavior in such applications, elucidating how consumers interact within these platforms. We analyzed 587 journal articles extracted from primary databases (Scopus and Web of Science), ultimately reviewing 112 articles spanning from 2014 to August 2023. Furthermore, we developed a conceptual framework to fully grasp the variables influencing consumer behavior, showcasing frequently reported factors in food delivery application literature. This research also identifies nine directions for further exploration, including regional and country comparisons, methodological approaches, theoretical perspectives, demographic analyses, independent variables, moderating effects, affective and cognitive evaluations, outcome responses, and drone-based food delivery application perspectives. This review is expected to offer valuable insights for both researchers and practitioners.